PENGARUH FLARE DAN CORONAL MASS EJECTION (CME) TERHADAP INDEKS Dst GEOMAGNET DAN FoF2 IONOSFER DI ATAS TANJUNGSARI SUMEDANG - Tiar Dani (Pusbindiklat - LIPI, 2009)
This research was conducted to see the effect ofsolarflare and Coronal Mass Ejection (CME) on geomagnetic and ionosphere above Tanjungsari, Sumedang, West Java. By using Disturbance storm time (Dst) index data for geomagnetic disturbance parameter and critical frequency (fo) of F2 ionosphere layer data for ionosphere disturbance parameter; a graph was plotted between occurrence off lare and CME with Dst index andf oF2 from year 2000 to 2003. The result found thatf lare and CME affect disturbance on geomagnetic caused a geomagnetic storm and disturbance on ionosphere cause an ionosphere storm. Those storms were depended by flare class, CME type, and its position on the sun when they happened Flare and CME event that happened also required time to reach the Earth.